Osteochondral autograft transplantation for juvenile osteochondritis dissecans of the knee: a series of twelve cases - Sasaki, Ken (Springer-Verlag, 2012)
PURPOSE: The purpose of this study was to evaluate the clinical outcomes of osteochondral autograft transplantation (OAT) for juvenile osteochondritis dissecans (JOCD) lesions of the knee, especially time to return to sports. METHODS: Twelve knee JOCD lesions with OCD grade 3 and 4 categorised by magnetic resonance imaging (MRI) were treated with OAT. Nine male and two female skeletally immature patients averaging 13.7 years old were included. The OCD lesions were assessed arthroscopically and then fixed in situ using multiple osteochondral plugs harvested under fluoroscopy from the distal femoral condyle without damaging the physis. International Cartilage Repair Society (ICRS) score and Lysholm score were assessed pre- and postoperatively. RESULTS: After a mean follow-up of 26.2 ± 15.1 months, the International Knee Documentation Committee (IKDC) subjective score significantly improved (p < 0.01). According to the IKDC score, objective assessment showed that ten of 12 (83 %) had excellent results (score: A) after OAT and significantly improved (p < 0.01). Based on ICRS criteria, results were satisfactory in all patients. No patients experienced complications at the graft harvest site. All patients returned to their previous level of athletic activity at an average of 5.7 months after the surgery. CONCLUSIONS: OAT for JOCD of the knee provided satisfactory results in all patients at a mean follow-up of 26.2 months.